Systematic Literature Review: The Effectiveness of PQ4R-Based E-LKPD on Elementary School Students’ Reading Comprehension Skills - Dina Noviyanti Arifah; Nidya Chandra Muji Utami; Apit Dulyapit (MASI Mandiri Edukasi, 2026)
Reading comprehension skills are essential in Indonesian language learning at the elementary school level, yet many students still struggle with inferential and evaluative aspects of comprehension. This study aims to analyze the effectiveness of PQ4R (Preview, Question, Read, Reflect, Recite, Review)-based e-LKPD in improving elementary school students’ reading comprehension skills. The research employed a Systematic Literature Review (SLR) method. Articles were collected from Google Scholar and reputable national and international journals published between 2019 and 2025 using relevant keywords. The selection process followed inclusion and exclusion criteria and applied the PRISMA stages, resulting in 15 eligible articles for systematic analysis. The findings indicate that PQ4R-based e-LKPD consistently has a positive impact on students’ reading comprehension skills, particularly in identifying main ideas, understanding textual meaning, making inferences, and enhancing learning engagement. The integration of e-LKPD facilitates the structured implementation of PQ4R stages in a more interactive, systematic manner than conventional printed worksheets. However, several challenges were identified, including limited technological infrastructure, teachers’ readiness in developing digital teaching materials, and variations in students’ digital literacy levels. In conclusion, PQ4R-based e-LKPD is an effective and innovative instructional tool for improving elementary school students’ reading comprehension, provided adequate technological support and teacher training are available.